(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
“From Labor Room to Labor Market: The Paradox of Motherhood and Gender Exploitation in Nigeria’s Baby Factories” explores the disturbing rise of baby factories in Nigeria, linking them to deeply entrenched patriarchal and capitalist structures. This article reveals how societal pressure on women to bear children, coupled with the stigmatization of infertility and out-of-wedlock pregnancy, fuels the demand for illicit child acquisition. Vulnerable young women, often economically disadvantaged and socially marginalized, are lured or forced into these exploitative facilities under false pretenses of employment or shelter. The baby factories in Nigeria operate as clandestine networks where women’s reproductive labor is commodified—turning motherhood into a transactional enterprise. The exploitation is intensified by capitalist motives, which reduce women to reproductive vessels and newborns to marketable goods. Male children, valued more highly, reflect patriarchal gender preferences. The article critiques how women’s reproductive agency is stripped away, situating baby factories within a broader context of reproductive slavery and gendered economic violence. Drawing on Marxist feminist theory, the author argues that capitalism and patriarchy jointly sustain the exploitation, perpetuating a cycle of poverty, dehumanization, and trafficking. The essay calls for systemic change—advocating for sex education, economic empowerment, legal reform, and public awareness to dismantle the structures enabling this crisis. Ultimately, the article asserts that ending baby factories requires confronting the intersectional injustices of gender, capitalism, and poverty to restore women’s dignity and ensure reproductive rights and justice. The fight against baby factories is a fight for human rights and social equity.